Research in personnel and human resources management. Volume 29 - Liao, Hui, 1975-; Martocchio, Joseph J.; Joshi, Aparna (Emerald, 2010)
This series publishes monograph length conceptual papers designed to promote theory and research on important substantive and methodological topics in the field of human resources management. Volume 29 of Research in Personnel and Human Resources Management (RPHRM) contains seven papers on important issues in the field of human resources management, thus continuing the tradition of the series to develop a more informed understanding of the field. This collection of papers represents excellent scholarship and illustrates the truly interdisciplinary character of the field.
Keywords: Business & Economics -- Human Resources & Personnel Management.; Business & Economics -- Management.; Business & Economics -- Organizational Behavior.; Personnel & human resources management.; Management of specific areas.; Personnel management.; elektronické knihy; electronic books